The effect of green spaces (neighborhood park) on the mental health (happiness) of the residents, case study of Mirdamad and Maghsodieh neighborhoods in Tabriz city - Amirreza Hashempoor; Mohammadreza Ezzatimehr (مهندسی و مدیریت ساخت, 2021)
The World Health Organization considers the environment to be influential on people's mental health. Ignoring the influential aspects of the built environment on the mental health of citizens has caused the formation of various mental and emotional problems for people in the society. The existence of stress, aggression, irritability, depression, boredom and physical complaints are the results of such conditions. Therefore, the aim of the current research is to investigate and explain the effect of the presence of green spaces (parks within the neighborhood) on mental health and happiness. To achieve this goal, two neighborhoods of Mirdamad (with sufficient and suitable green spaces) and Maqsodieh neighborhood (without sufficient green spaces) in The agenda has been set. According to the topic of the research, the goal of the research has been formed in line with the research questions. It has been done in the residential areas of Mirdamad and Maqsoodieh at 1398-1399. To determine the level of happiness, the combination of two happiness measurement tools, Oxford and Fordyce, has been used. Then the data obtained has been analyzed by SPSS software and using descriptive statistics. The analysis of the data showed that there is a significant difference between the level of happiness of residents of residential areas and the level of access to green spaces and parks within the neighborhood. This means that the greater the level of access to green spaces within the neighborhood of residential areas, the higher the number of residential units. Residents have a higher level of happiness.